1978
DOI: 10.1136/hrt.40.12.1408
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid atresia. Clinical course in 62 cases (1967--1974).

Abstract: Tricuspid atresia constitutes 1 to 3 per cent of all congenital cardiac lesions (Nadas and Fyler, 1972). Diagnosis is usually obvious from electrocardiographic, radiological, and echocardiographic features. Long-term survival without palliative procedure is unlikely (Campbell, 1961). Recent advances in surgical treatment (Fontan and Baudet, 1971;Kreutzer et al., 1973) have prompted us to review the outcome in a group of patients with tricupsid atresia in order to identify those suitable for a Fontan procedure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…51 The scope of these papers is such that the authors could not provide further details on these patients. [49][50][51] Partial closure of VSD in tricuspid atresia has been reported previously. 25,30,41,52,53 Gallaher and Fyler reported three patients with tricuspid atresia who had cardiac failure and pulmonary plethora during infancy; over varying periods of time they became more cyanotic; cardiomegaly and pulmonary blood flow decreased; finally they required palliative shunt procedures to relieve symptoms of hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…51 The scope of these papers is such that the authors could not provide further details on these patients. [49][50][51] Partial closure of VSD in tricuspid atresia has been reported previously. 25,30,41,52,53 Gallaher and Fyler reported three patients with tricuspid atresia who had cardiac failure and pulmonary plethora during infancy; over varying periods of time they became more cyanotic; cardiomegaly and pulmonary blood flow decreased; finally they required palliative shunt procedures to relieve symptoms of hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51] Dick et al found one patient with complete closure (documented by autopsy) among 101 patients with tricuspid atresia reviewed. 49 Patel and associates, in a review of 62 patients with tricuspid atresia, found two cases with complete spontaneous closure of VSD; both closures were documented by angiography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 5 of these 14 lived beyond the 2nd year of age, with 6 dying within the first year of life, 1 at the time of banding and the other 5 without having any form of palliation and dying in severe congestive heart failure. Patel et al 92 also reported the clinical course of patients with tricuspid atresia seen between 1967 and 1974. Of 6 patients requiring banding, 2 died.…”
Section: Analysis Of Outcomesmentioning
confidence: 99%
“…Any number of surgical manoeuvres have been used to palliate the patient with a dominant left ventricle, discordant ventriculo-arterial connections, and unobstructed flow of blood into the lungs. [6][7][8][9][10][11]27,31,33,[35][36][37][38][39]42,43,[45][46][47][48][49][50]62,66,[85][86][87][88][89][90][91][92][93][94][95][96]115,116,122 Some of these are now of historical interest only, and were performed either prior to or at the beginning of the era of Fontan surgery and thus before we became aware of the significance of myocardial hypertrophy. With increasing recognition and concern about the impact of obstruction to the systemic ventricular outflow tract and the development of myocardial hypertrophy, a number of surgical "solutions" were suggested to treat the subaortic stenosis, or indeed to prevent its occurrence ( Table 2).…”
Section: Surgical Manoeuvres Preventing Systemic Obstructionmentioning
confidence: 99%